Ag-Doped TiO2 Nanotube Arrays Composite Film as a Photoanode for Enhancing the Photoelectric Conversion Efficiency in DSSCs. (8th September 2016) - Hu, Jinghua; Cheng, Jiejie; Tong, Shengqiang; Yang, Yingping; Chen, Mengwei; Hu, Shiwu
Abstract : A Ag-doped double-layer composite film with TiO2 nanoparticles (P25) as the underlayer and TiO2 nanotube (TNT) arrays with the Ag-doped nanoparticles as the overlayer was fabricated as the photoanode in dye-sensitized solar cells (DSSCs). Five different concentrations of Ag-doped TNT arrays photoelectrode were compared with the pure TNT arrays composite photoelectrode. It is found that the photoelectric conversion efficiency of the TNT arrays composite photoanode is gradually improved from 3.00% of the pure TNT arrays composite photoanode to 6.12% of the Ag-doped TNT arrays photoanode with the increasing of the doping concentration, reaching up to the maximum in the 0.04 mol/L AgNO3 solution, and then slightly decreased to 5.43% after continuing to increase the doping concentration. The reason is mainly that the cluster structure of the Ag nanoparticles with large surface area contributes to dye adsorption and the Surface Plasmon Resonance Effect of the Ag nanoparticles improved the photocatalytic ability of the TNT arrays film.